Genome-wide association study identifies candidate loci associated with chronic pain and postherpetic neuralgia. (March 2021) - Nishizawa, Daisuke; Iseki, Masako; Arita, Hideko; Hanaoka, Kazuo; Yajima, Choku; Kato, Jitsu; Ogawa, Setsuro; Hiranuma, Ayako; Kasai, Shinya; Hasegawa, Junko; Hayashida, Masakazu; Ikeda, Kazutaka
Background: Human twin studies and other studies have indicated that chronic pain has heritability that ranges from 30% to 70%. We aimed to identify potential genetic variants that contribute to the susceptibility to chronic pain and efficacy of administered drugs. We conducted genome-wide association studies (GWASs) using whole-genome genotyping arrays with more than 700, 000 markers in 191 chronic pain patients and a subgroup of 89 patients with postherpetic neuralgia (PHN) in addition to 282 healthy control subjects in several genetic models, followed by additional gene-based and gene-set analyses of the same phenotypes. We also performed a GWAS for the efficacy of drugs for the treatment of pain. Results: Although none of the single-nucleotide polymorphisms (SNPs) were found to be genome-wide significantly associated with chronic pain ( p  ≥ 1.858 × 10 −7 ), the GWAS of PHN patients revealed that the rs4773840 SNP within the ABCC4 gene region was significantly associated with PHN in the trend model (nominal p  = 1.638 × 10 −7 ). In the additional gene-based analysis, one gene, PRKCQ, was significantly associated with chronic pain in the trend model (adjusted p  = 0.03722). In the gene-set analysis, several gene sets were significantly associated with chronic pain and PHN. No SNPs were significantly associated with the efficacy of any of types of drugs in any of the genetic models. Conclusions: These results suggest that the PRKCQ gene and rs4773840 SNP within the ABCC4 gene region may be related to the susceptibility to chronic pain conditions and PHN, respectively.